Exploring Meta-Analyses: An Example. - Moore, Randall F. (Psychiatric Times, 2022)
The article addresses methodological and statistical concerns about the study "The Serotonin Theory of Depression: A Systematic Umbrella Review of the Evidence." It identifies misrepresented statistics in the study including confidence interval measures, prediction interval, heterogeneity measure and effect sizes. It points out the failure of the study to address the role of serotonin in loss of neuroplasticity in depression.